Policy-Oriented Technology Assessment Across Europe Expanding Capacities - Klüver, Lars; Øjvind Nielsen, Rasmus; Jørgensen, Marie Louise (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book is open access under a CC-BY license. Policy-making to address grand challenges faces greater complexity than any previous project of modernization. Future scenarios are haunted by uncertainty and there is real ambivalence as to the values that policy should strive for. In this situation decision-makers look to research and innovation to provide answers and solutions. But neither can the great transitions ahead be planned by science, nor will conventional methods of innovation bring such transitions about. A turn to interactive governance is therefore underway with policy-makers and citizens becoming increasingly involved in processes of deliberating futures. Technology Assessment (TA) is the art of structuring such processes. TA goes beyond traditional expert policy analysis by systematically combining a multi-disciplinary evidence base with participatory approaches to policy deliberation. TA thus seeks to act as a hub for serious and transparent dialogue between policy, industry, science, and society about the challenges ahead and the available options for overcoming them responsibly. This volume offers an up-to-date account of the expansion of technology assessment capacities across new European member states. The contributions of this volume are written by leading European researchers and practitioners in technology assessment (TA) and are based on the PACITA (Parliaments and Civil Society in Technology Assessment) project. Lars Klüver is Director of the Danish Board of Technology, Copenhagen, Denmark. Rasmus Øjvind Nielsen is Researcher at the Danish Board of Technology, Copenhagen, Denmark. Marie Louise Jørgensen is Project Manager at the Danish Board of Technology, Copenhagen, Denmark.